A proposed collection development policy for the Gender and Development Library of the Philippine Broadcasting Services - Dela Cruz, Jose A. Jr (2005)
The Philippine Broadcasting Service - Bureau of Broadcast Services (PBS-BBS) is the official radio broadcast arm of the Philippine government. The PBS-BBS) is the official radio broadcast arm of the Philippine government. The PBS-BBS established the Gender and development (GAD) Library to be able to recognize the role of women in the development of the nation. With the early establishment of the library it seems that the library has its weaknesses to address.